Accounting for Iranian EFL Teachers' Burnout: Educational Beliefs and Teacher Self-Disclosure in Focus - Mohammad Ali Ayatollahi; Ali Reza Nemati; Al Tiyb Suliman Al Khaiyali (Universitas Islam Negeri Walisongo Semarang, 2022)
Teaching is considered a high-risk profession for those suffering from burnout syndrome. Burnout syndrome affects the person who suffers from it and everyone around them, e.g., family, friends, co-workers, students, and parents. The main purpose of this study was to investigate any probable relationship between Iranian EFL teachers’ educational belief and their tendency to self-disclose with their likelihood of suffering from burnout. The research instruments were The Teacher Self-Disclosure Scale (Cayanus Martin, 2008), Maslach Burnout Inventory (MBI-ES) (Maslach, C., Schaufeli, 1993), and the Teachers' Educational Belief Questionnaire. The participants were 98 EFL teachers selected from 25 private language schools in Shiraz, Iran. Descriptive statistics, Cronbach Alpha coefficients, and Person Product-Moment Correlation Coefficient were used to answer this research question. Analyzing the data collected through the questionnaires indicated a positive correlation between some dimensions of teacher burnout and teachers’ constructive or traditional beliefs. Thus, ‘lack of personal achievement’ and ‘constructive beliefs’, ‘emotional exhaustion’ and ‘depersonalization’, and teachers’ traditional beliefs were positively correlated. On the contrary, a negative correlation was identified between ‘lack of personal achievement’ and teachers’ traditional beliefs. Likewise, ‘emotional exhaustion’ and ‘depersonalization’ on the burnout scale were correlated with teachers’ constructive beliefs. However, no significant correlation was observed between teachers’ neutral beliefs and any dimensions of the burnout scale. Moreover, teacher self-disclosure quantity and negativity were correlated with ‘emotional exhaustion’ and ‘depersonalization’ on the burnout scale.